2019
DOI: 10.5194/esd-10-859-2019
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress risk in European dairy cattle husbandry under different climate change scenarios – uncertainties and potential impacts

Abstract: Abstract. In the last decades, a global warming trend was observed. Along with the temperature increase, modifications in the humidity and wind regime amplify the regional and local impacts on livestock husbandry. Direct impacts include the occurrence of climatic stress conditions. In Europe, cows are economically highly relevant and are mainly kept in naturally ventilated buildings that are most susceptible to climate change. The high-yielding cows are particularly vulnerable to heat stress. Modifications in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 88 publications
1
60
0
3
Order By: Relevance
“…Thus, 6687 hourly values of gas concentrations per sample line were available for this study. As additional parameters, indoor temperature and relative humidity were measured with four EasyLog USB 2+ sensors (Lascar Electronics Inc., Whiteparish, UK) at a height of approximately 3 m [2]. Animal parameters, such as the number of cows in the barn (355 lactating Holstein-Friesian on average, no dry), cow mass (682 kg on average), and milk yield (39.2 kg day −1 on average) were provided as daily herd averages by the administration of the barn.…”
Section: Measurement Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 6687 hourly values of gas concentrations per sample line were available for this study. As additional parameters, indoor temperature and relative humidity were measured with four EasyLog USB 2+ sensors (Lascar Electronics Inc., Whiteparish, UK) at a height of approximately 3 m [2]. Animal parameters, such as the number of cows in the barn (355 lactating Holstein-Friesian on average, no dry), cow mass (682 kg on average), and milk yield (39.2 kg day −1 on average) were provided as daily herd averages by the administration of the barn.…”
Section: Measurement Setupmentioning
confidence: 99%
“…National and international directives, such as the EU-28 National Emission Ceilings (NEC, see https://www.eea.europa.eu, last access 16 December, 2019), urge for a substantial reduction of airborne pollutants in order to limit climate change and protect the environment and human health [1,2]. The evaluation of emission reduction measures requires a reliable quantification of pollutant gas emissions in all economic sectors, including agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Global warming and climate change are among the biggest issues facing the world, and their economic impact on dairy farming is a relevant issue. The reduction in milk yield related to heat stress has led to estimated losses of 5.4% of the monthly income of farmers during summer [ 1 ]. This impact is expected to significantly increase in the future, with the annual average land temperature in Europe expected to increase by 1.0–5.5 °C by the end of the century [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that animals staying at the leeward side of the feeding alley may have less fresh air than those staying at the windward side. However, the animal comfort will be different depending on the jet of cold air [4] or warm air [33]. The small or weaker jets which could not go through roof opening created a recirculation zone below the windward roof.…”
Section: Calculation Of Airflow Rate and Non-dimensional Airflow Ratementioning
confidence: 99%